Amateur-recordings of the developments around the German reunification, such as Künstlerdemo, Kohl in Dresden, Neustadt and anti-Stasi-slogans
Amateur-recordings of the developments around the German reunification, such as Künstlerdemo, Kohl in Dresden, Neustadt and anti-Stasi-slogans.